Mapping lifecycle management activities for blockbuster drugs in Japan based on drug approvals and patent term extensions. Issue 2 (February 2016) - Yamanaka, Takayuki; Kano, Shingo
Highlights: A novel quantitative framework of drug LCM is provided. Effective drug LCM involves diverse drug approvals and multiple patent term extensions. The LCM for blockbuster drugs in Japan fall into 3 categories. The strategy for selecting a suitable LCM approach among these 3 types. Abstract : Drug lifecycle management (LCM), which entails acquiring drug approvals and patent protections, contributes to maximizing drug discovery investment returns. In a previous survey, a comparative analysis between Japan and the USA indicated that a unique patent term extension system has an important role in Japanese drug LCM. Therefore, in this survey, we focused on drug approvals and patent term extensions, and found that the LCM for blockbuster drugs in Japan can be categorized into three types (drug approval-oriented LCM, patent term extension-oriented LCM, and inactive-type LCM), of which the first two have been implemented recently. Here, we suggest a strategy for selecting a suitable LCM approach among these three types based on the prospects for drug improvements.